2008
DOI: 10.1248/cpb.56.1367
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Synthetic Reactions for Nitrogen-Containing Compounds and Their Application

Abstract: Nitrogen-containing compounds are core parts not only of natural and synthetic medicines but also of biologically active compounds including natural products. This review focuses on the development of new synthetic reactions for nitrogen-containing compounds via three methodologies: the reductive photocycloaddition reaction of enamides, radical addition reaction, and nucleophilic addition reaction. Newly developed reactions were successfully applied to the synthesis of various types of nitrogen-containing comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…Naito et al, has previously reported the use of triethylborane (Et 3 B/air) as a radical initiator in the intermolecular radical reactions on solid support [5]. The work to date has been extended to tandem radical addition-cyclization of oxime ethers anchored to polymer support.…”
Section: Peg-bound Reagents and Free Radical Transformations Up To Damentioning
confidence: 99%
“…Naito et al, has previously reported the use of triethylborane (Et 3 B/air) as a radical initiator in the intermolecular radical reactions on solid support [5]. The work to date has been extended to tandem radical addition-cyclization of oxime ethers anchored to polymer support.…”
Section: Peg-bound Reagents and Free Radical Transformations Up To Damentioning
confidence: 99%
“…Compounds contain nitrogen in their cyclic structure exists numerous biologically active moieties and exhibit numerous application's in chemistry, biology, and other sciences [1][2][3][4][5][6] . Oxadiazines are the molecules with oxygen and two nitrogen rest in different positions of the cyclic structure.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen compounds and heterocycles are also basic constituents of many natural and synthetic medicines, as well as of biologically active compounds, including natural products (Naito, 2008;Martins et al, 2015).…”
Section: Introductionmentioning
confidence: 99%